Komunikasi Keluarga Tiri antara Anak Remaja Perempuan dengan Ibu Tiri - Pratyaksa, Cintya; Pudjo Santosa, Hedi (Interaksi Online, 2019)
Family communication is a form of interpersonal communication that is very specific. Communication in the family can experience movement and change because of the nature of communication that is not static and non-linear. Parental divorce can change the pattern of family communication to be more complex especially for the children. Moreover, if one divorced parent remarries and forms a step family, stepfamily communication will be formed. The aims of this study is to understand and illustrate how is young women’s experiences in build relationships with stepmother within stepfamilies and how stepfamily communication between the young women and the stepmothers is interwoven. This study found that in the experience of young women who have relationships with stepmothers in stepfamilies, there is interpersonal communication involved. This communication pattern can be seen from the intensity of young women and stepmothers communicating, the smooth communication between them, the openness of communication between the two, and the familiarity of communication that exists between young women and stepmothers. This study also revealed that stepmothers as substitute figures of biological mothers in stepfamilies are expected to be able to carry out the role of care and care which includes giving the role of affection, role in discipline and educating children, and the role of housewives. The role performed by stepmothers in stepfamilies can form a pattern of relationships with young women where in this relationship will be seen how close the relationship between young women with stepmothers and how they maintaining their relationships.